Altered FoF1 ATP synthase and susceptibility to mitochondrial permeability transition pore during ischaemia and reperfusion in aging cardiomyocytes - Fernandez-Sanz, Celia; Ruiz-Meana, Marisol; Castellano, José; Miro-Casas, Elisabet; Nuñez, Estefanía; Inserte, Javier; Vázquez, Jesús; Garcia-Dorado, David (Thrombosis and Haemostasis, 2015)
Aging is a major determinant of the incidence and severity of ischaemic heart disease. Preclinical information suggests the existence of intrinsic cellular alterations that contribute to ischaemic susceptibility in senescent myocardium, by mechanisms not well established. We investigated the role of altered mitochondrial function in the adverse effect of aging. Isolated perfused hearts from old mice (> 20 months) displayed increased ischaemia-reperfusion injury as compared to hearts from adult mice (6 months) despite delayed onset of ischaemic rigor contracture. In cardiomyocytes from aging hearts there was a more rapid decline of mitochondrial membrane potential (ΔΨm) as compared to young ones, but ischaemic rigor shortening was also delayed. Transient recovery of ΔΨm observed during ischaemia, secondary to the reversal of mitochondrial FoF1 ATP synthase to ATPase mode, was markedly reduced in aging cardiomyocytes. Proteomic analysis demonstrated increased oxidation of different subunits of ATP synthase. Altered bionergetics in aging cells was associated with reduced mitochondrial calcium uptake and more severe cytosolic calcium overload during ischaemia-reperfusion. Despite attenuated ROS burst and mitochondrial calcium overload, mitochondrial permeability transition pore (mPTP) opening and cell death was increased in reperfused aged cells. In vitro studies demonstrated a significantly reduced calcium retention capacity in interfibrillar mitochondria from aging hearts. Our results identify altered FoF1 ATP synthase and increased sensitivity of mitochondria to undergo mPTP opening as important determinants of the reduced tolerance to ischaemia-reperfusion in aging hearts. Because ATP synthase has been proposed to conform mPTP, it is tempting to hypothesise that oxidation of ATP synthase underlie both phenomena.
Keywords: Mitochondria; calcium; aging; bionergetics